2019
DOI: 10.3389/fphar.2019.00742
|View full text |Cite
|
Sign up to set email alerts
|

Soshiho-Tang, a Traditional Herbal Medicine, Alleviates Atopic Dermatitis Symptoms via Regulation of Inflammatory Mediators

Abstract: Soshiho-tang (SST) is a well-known traditional herbal medicine used for the treatment of many diseases. The aims of this study are to investigate the effects of SST on atopic dermatitis (AD) symptoms and to examine its mechanism. Human keratinocyte (HaCaT) cells were stimulated with tumor necrosis factor alpha (TNF-α)/IFN-γ to induce AD-like keratinocyte environment. 2,4-Dinitrochlorobenzene (DNCB) was used to induce AD-like skin lesions in the dorsal skin of BALB/c mice. SST and dexamethasone were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
(55 reference statements)
1
22
0
1
Order By: Relevance
“…Previously, a potential of SST has been reported as anti-inflammatory medication in various diseases such as asthma, atopic dermatitis and liver injury. 6 , 7 , 8 These reports may support to address the main mechanisms thereby protecting neuronal damages by the SST treatment through activation of the proinflammation-related signaling pathways.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previously, a potential of SST has been reported as anti-inflammatory medication in various diseases such as asthma, atopic dermatitis and liver injury. 6 , 7 , 8 These reports may support to address the main mechanisms thereby protecting neuronal damages by the SST treatment through activation of the proinflammation-related signaling pathways.…”
Section: Discussionmentioning
confidence: 75%
“…SST was traditionally used to control febrile diseases in several Asian countries. 1 Recent studies support the notion that SST has potential anti-tumor, 2 , 3 , 4 , 5 anti-inflammatory, 6 , 7 , 8 immune regulatory, 9 , 10 and hepatoprotective 5 , 7 activities in preclinical investigations. Most clinical studies using SST have shown its efficacy for liver problems such as hepatic dysfunction, 11 chronic liver diseases, 12 hepatitis B and C, 13 , 14 and liver cancer.…”
Section: Introductionmentioning
confidence: 85%
“…It was previously indicated that induction of HO-1 plays a protective role in several inflammation-related diseases (7), including AD, and HO-1 has been reported to exhibit therapeutic efficiency in AD (8)(9)(10)(11). Chen and Zhong (16) revealed that HO-1 combined with microRNAs may affect certain skin diseases, such as ischemia, hypoxia, rheumatoid arthritis and AD, by regulating the functions of T cells, dendritic cells and mast cells, and the release of chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) catalyzes the first and rate-limiting step in the oxidative degradation of free heme, and may affect several biological processes of aneurysmal diseases, articular diseases and hepatic gluconeogenesis, among others, via its enzymatic by-products (7). Previous studies on AD mouse models have demonstrated that certain agents, including Soshiho-tang, sulforaphane, dihydroaustrasulfone alcohol (WA-25) and Platycodon grandiflorus root-derived saponins, can alleviate AD-like skin lesions and skin inflammation by increasing the expression of HO-1 and nuclear factor erythroid 2-related factor 2 (Nrf2) (8)(9)(10)(11). Another study also concluded that enhancement of HO-1 expression attenuated the development of skin lesions in mice (12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the treatment of atopic dermatitis requires better and safer therapy. Several lines of evidence have suggested the possible application of avonoidenriched herbal product in treating dermatitis [5,6,13,14].…”
Section: Introductionmentioning
confidence: 99%